Um percurso diacrônico sobre as articulações entre ética e estética na semiótica de A. J. Greimas - Sbabo, Alexandre Provin (2020)
This research aims to study how ethics and aesthetics are articulated in semiotics of structuralist origin, from the perspective of a diachronic path based on the theoretical and methodological developments carried out by Algirdas Julien Greimas. The bibliographic and diachronic study is organized based on the dates of publication of the author’s works and according to their relation with the problem of the articulation of ethics and aesthetics in the development of his theory, covering more than 40 years of intellectual production and computing work from its most diverse phases - from before he used the term semiotics to his last individual work. Our objective is to follow the path of the development of the theoretical and methodological framework of A. J. Greimas so that we can highlight the processes that allowed the constitution of analytical models capable of understanding the articulations of aesthetic values and ethical values in the most diverse objects and interactions - from mythical narratives to abstract paintings and interactions between subjects. The hypotheses to be tested are the following: (I) ethics and aesthetics are related to the question of signification, construction and apprehension of meaning; (II) the articulation of ethics and aesthetics constitutes the basis of the questions of the semiotic methodology; (III) the issue of ethics and aesthetics is present in the thought of Greimas since his first works; (IV) the articulation proposed by semiotics between these concepts performs both a hypotactic and hyponymic approach. Thus, the importance of this work lies in the possibility of visualizing the interactions between these two terms through semiotic structures that define and articulate ethics and aesthetics, as well as the isomorphism between the content plan and the expression plan. This path reconstructed the network of formal relations thought by Greimas, able to illustrate the presence of ethics and aesthetics in the different interactions and objects, as well as highlight the treatment given by semiotics in the articulation of these concepts for the construction and apprehension of meaning